On-board safety systems: Enablement of management and logistics - John Woodrooffe (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
On-board commercial vehicle safety technologies present new opportunities for management and logistics in the road transport industry. As with many emerging technologies, the link to opportunity beyond the designed purpose of a particular technology is not fully realised until after implementation. This paper explores the relationship between on-board safety technology, management and logistics within the trucking industry. Topics discussed include best practice fleet safety management, safety culture, safety-related technologies. It includes the results of a survey of fleet safety executives and drivers about the effectiveness of safety technologies and effectiveness ranking. A literature review on the effectiveness of fleet management techniques that encourage safety culture and performance is included. The ability for on-board safety systems to support logistics and multimodal transport are discussed. Of the technologies currently available, electronic logging devices were found to be the most promising technology for transformational change in the context of safety, management and logistics.
Keywords: 330; Lastkraftwagen; Verkehrssicherheit; Sicherheitstechnik; Fahrzeugflotte; Transportmanagement